Consumption and Keynesian fiscal policy - Alfredo Schclarek (Center for Economic Studies and ifo Institute (CESifo), 2004)
This paper empirically studies the effects of fiscal policy shocks on private consumption. Further, it tries to determine if the level of government bond yield and the unemployment rate affect that relationship. We use yearly data between 1970 and 2000 for thirty-eight countries, of which half are industrialized and half are developing countries. In general, the estimation results seem to indicate that government consumption shocks have Keynesian effects for both industrial and developing countries. In the case of tax shocks, the evidence suggest that they do not have any effects on private consumption. Furthermore, there is no evidence that favors the hypothesis of expansionary fiscal consolidations.
Keywords: E21; C33; E62; 330; fiscal policy; private consumption; government expenditure; taxation; developing countries; Antizyklische Finanzpolitik; Öffentliche Ausgaben; Schock; Gesamtwirtschaftlicher Konsum; Schätzung; Welt